2015
DOI: 10.1248/cpb.c15-00487
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Fluorinated Carbon Acids: Synthesis, Physicochemical Properties, and Catalysis

Abstract: The bis[(trifluoromethyl)sulfonyl]methyl (Tf 2 CH; Tf SO 2 CF 3 ) group is known to be one of the strongest carbon acid functionalities. The acidity of such carbon acids in the gas phase is stronger than that of sulfuric acid. Our recent investigations have demonstrated that this type of carbon acids work as novel acid catalysts. In this paper, recent achievements in carbon acid chemistry by our research group, including synthesis, physicochemical properties, and catalysis, are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The reaction of 4f with 2.0 equiv of p-cresol in acetonitrile went to completion within only 10 min at room temperature. 1 HNMR analysiso ft he crude material showed clean formation of the desired carbon acid 8a and 2-fluoropyridine (7). This resulte videncest hat 4f smoothly produces Tf 2 C=CH 2 (2a).…”
Section: Synthesis Of Strongly Acidic Carbon-acid Derivativesmentioning
confidence: 66%
See 2 more Smart Citations
“…The reaction of 4f with 2.0 equiv of p-cresol in acetonitrile went to completion within only 10 min at room temperature. 1 HNMR analysiso ft he crude material showed clean formation of the desired carbon acid 8a and 2-fluoropyridine (7). This resulte videncest hat 4f smoothly produces Tf 2 C=CH 2 (2a).…”
Section: Synthesis Of Strongly Acidic Carbon-acid Derivativesmentioning
confidence: 66%
“…2017, 23,8203 -8211 www.chemeurj.org virtually nonbasic compound. In the synthesis of strongly acidic carbon acids and their derivatives, the fact that 2-fluoropyridine (7)c an be easily removed by evaporation playeda n important role. Secondly,n oa cidic speciesw ere present in this equilibrium mixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original protocol by Alcaide and Almendros, [12] zwitterionic reagent 4 was adopted as a source for Tf 2 C=CH 2 . On the other hand, here we found that the desired molecular transformation smoothly proceeded by mixing Tf 2 CH 2 3 , paraformaldehyde, and diphenylacetylene in 1,2‐dichloroethane (DCE) under gently heating conditions to give the cyclobutene product 5 a in an excellent yield [18] . According to this precedure, we prepared several gem ‐bis(triflyl)cyclobutenes needed in this work ( vide infra ).…”
Section: Resultsmentioning
confidence: 87%
“…[5] The author has studied synthesis, acidity evaluation and catalytic usage of such strong carbon acids. [6] The development of new strong acids leads to stable anionic species (Figure 1). In the first report by Haszeldine and co-workers, [3b] it was mentioned that bis(triflyl)methane 1 a produced the corresponding sodium and silver salts by neutralisation.…”
Section: Introductionmentioning
confidence: 99%